2021
DOI: 10.1002/hep.32029
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Factor SLU7 Prevents Oxidative Stress‐Mediated Hepatocyte Nuclear Factor 4α Degradation, Preserving Hepatic Differentiation and Protecting From Liver Damage

Abstract: name: HEPACARE; AECC post-doctoral fellowship to MA (POSTD18014AREC); Ministerio de Educación FPU fellowship to MGR (FPU18/01461); Ministerio de Educación FPI fellowship to MR (BES-2017-079883); Ramón y Cajal Program contract to MGFB (RYC2018-024475-1); Fundación Eugenio Rodríguez Pascual; Fundación Mario Losantos; Fundación M Torres and the generous donation of Mr. Eduardo Avila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 56 publications
1
27
0
7
Order By: Relevance
“…We also demonstrated how HNF4 protein stability can be critically regulated by a novel antioxidant role of SLU7 in hepatocytes [117]. Consequently, the downregulation of SLU7 in mouse liver results in the reduced expression of P1 promoter HNF4 isoforms, and enhanced P2 promoter activity, a response exacerbated during chronic liver injury [76,117].…”
Section: Loss Of Hepatic Function In Liver Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…We also demonstrated how HNF4 protein stability can be critically regulated by a novel antioxidant role of SLU7 in hepatocytes [117]. Consequently, the downregulation of SLU7 in mouse liver results in the reduced expression of P1 promoter HNF4 isoforms, and enhanced P2 promoter activity, a response exacerbated during chronic liver injury [76,117].…”
Section: Loss Of Hepatic Function In Liver Diseasementioning
confidence: 84%
“…Interestingly, in that early study we also described how TGF downregulated HNF4 levels in hepatocytes through the induction of the transcription factor Wilm's tumor 1 (WT1), a fetal gene reactivated during hepatocellular dedifferentiation in human cirrhosis [94,112]. Since then, a plethora of studies have confirmed and extended these original findings, describing the impairment of HNF4 expression and regulatory activity in human chronic liver disease of viral, alcoholic or metabolic origin [49,54,89,90,[113][114][115], as well as in acute liver failure [54,63,116,117]. Complementary studies in human tissues and experimental models also identified changes in the ratio of HNF4 P1-and J o u r n a l P r e -p r o o f P2-derived isoforms and in HNF4 subcellular localization [118].…”
Section: Loss Of Hepatic Function In Liver Diseasementioning
confidence: 91%
“…In both human and animal models, the step II splicing regulator SLU7 has been found down-regulated in HCC, as well as in preneoplastic conditions, such as liver cirrhosis [ 66 , 67 ]. The reduced SLU7 expression has been associated with the activation of the epidermal growth factor receptor (EGFR) by its ligand amphiregulin (AREG) during inflammation [ 66 ], which has also been linked to the down-regulation of other splicing regulators, such as the SR protein SRSF3 [ 68 , 69 ].…”
Section: Liver Cancer-associated Alterations In the Spliceosome Machinerymentioning
confidence: 99%
“…Subsequent works identified its human homologue and characterized its role in the spliceosome [ 9 , 10 , 11 , 12 , 13 , 14 ], highlighting that SLU7 controls the diversity of gene transcripts in a cell. In addition, more recent findings have identified SLU7 also involved in other levels of gene expression regulation [ 15 , 16 , 17 , 18 , 19 , 20 ]. Specifically, SLU7 has been implicated in the epigenetic remodeling of DNA, in the modulation of the transcriptional activity and in controlling protein stability.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, SLU7 has been implicated in the epigenetic remodeling of DNA, in the modulation of the transcriptional activity and in controlling protein stability. All these findings identify SLU7 as a pleiotropic factor with a holistic function at different levels of gene expression regulation [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%